IDEOLOGI DAN KONSTITUSI DALAM PERKEMBANGAN NEGARA-BANGSA INDONESIA: REKONSTRUKSI TRADISI, DEKOLONISASI, DAN DEMOKRATISASI - Fitriciada Azhari, Aidul (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2013)
The research has purpose to investigate the development of Pancasila and the 1945 Constitution as the ideology and the constitution of Indonesia amidst the development of nation-state post-World War II and post-Cold War and its implication to position of people as a nation and citizens. With a socio-legal approach, the research found that the development of Pancasila and the 1945 Constitution has changed from the ideology and the constitution of postcolonial to the ideology and the constitution of post authoritarian. The change is marked by reduction of reconstruction of tradition and decolonization in the 1945 Constitution. Then, those are replaced by a purpose to democratization of the 1945 Constitution according to the universal values. The change that emphasizes on majority rule and rational choice also has shifted character of people from collectivity as a nation to individuality as a citizen.